Coordination Of Benefit (COB) Program Development Analysis: A Case Study Of Healthcare Insurance In Indonesia - Citrawati, Citrawati; Edy Suntoro, Eko; Puspitaloka Mahadewi, Erlina (Publisher Cv. Inara, 2023)
The present study reports the first comprehensive study on the coordination of benefits program in healthcare insurance in Indonesia. Every individual Indonesian citizen who works is required to have health insurance as a fulfillment of the obligation to be physically and comprehensively healthy. Ownership of health insurance can be through government programs which are mandatory government policies for every employee or health insurance managed by the services of a commercial insurance company. So that every Indonesian employee or citizen generally has 2 health insurance memberships, one is commercial insurance and the other is mandatory insurance from the government, BPJS health insurance. The use of health insurance from commercial insurance is the first choice, while BPJS health insurance is used as a backup if the coverage limit on commercial insurance has expired. With limited coverage limits provided by private insurance based on premium payments for each class registered by the company, the government facilitates a program to use the benefits of the two health insurances simultaneously, known as the Coordination of Benefits between BPJS Health and commercial insurance. This study uses a qualitative method to analyze how far this program has progressed, as well as the development of an additional health insurance benefit program in Indonesia. The end goal of this research it can be concluded that highlighting the benefits of this program that can be maximized by health insurance participants, what obstacles are faced by participants, as well as health services when using the coordination of benefits program and its development in the future.